ETIKA KOMUNIKASI DALAM ALâQURâAN - Khoiruddin, Muhammad (Universitas Djuanda, 2015)
Communication models used Allah in the Quran is a diversified communications model that is considered capable of affecting humans in general and applies all time therefore how we again take the example of the values of communication that exist in the Quran that messages in the Quran can be socialized to the maximum level of communication furthermore those values become basic need of human characters in whole life. The methodology utilized is text interpretation, since the basic language in the Holy Qurâan is Arabic, so then the interpretation and understanding would be compared to the Arabic system and the deep meaning of Arabic language, in order to encompass the core values and the contextual relationship of the objective in each word of the text. Therefore, this humble paper should be connected to the further research to gain the level of kindness in this worldly life and hereafter insya Allah.